Android Programming with Kotlin for Beginners - Horton, John; Safari, an O'Reilly Media Company (Packt Publishing, 2019)
Build smart looking Kotlin apps with UI and functionality for the Android platform Key Features Start your Android programming career, or just have fun publishing apps on Google Play marketplace The first-principle introduction to Kotlin through Android, to start building easy-to-use apps Learn by example and build four real-world apps and dozens of mini-apps Book Description Android is the most popular mobile operating system in the world and Kotlin has been declared by Google as a first-class programming language to build Android apps. With the imminent arrival of the most anticipated Android update, Android 10 (Q), this book gets you started building apps compatible with the latest version of Android. It adopts a project-style approach, where we focus on teaching the fundamentals of Android app development and the essentials of Kotlin by building three real-world apps and more than a dozen mini-apps. The book begins by giving you a strong grasp of how Kotlin and Android work together before gradually moving onto exploring the various Android APIs for building stunning apps for Android with ease. You will learn to make your apps more presentable using different layouts. You will dive deep into Kotlin programming concepts such as variables, functions, data structures, Object-Oriented code, and how to connect your Kotlin code to the UI. You will learn to add multilingual text so that your app is accessible to millions of more potential users. You will learn how animation, graphics, and sound effects work and are implemented in your Android app. By the end of the book, you will have sound knowledge about significant Kotlin programming concepts and start building your own fully featured Android apps. What you will learn Learn how Kotlin and Android work together Build a graphical drawing app using Object-Oriented Programming (OOP) principles Build beautiful, practical layouts using ScrollView, RecyclerView, NavigationView, ViewPager and CardView Write Kotlin code to manage an apps' data using different strategies including JSON and the built-in Android SQLite database Add user interaction, data captures, sound, and animation to your apps Implement dialog boxes to capture input from the user Build a simple database app that sorts and stores the user's data Who this book is for This book is for people who are new to Kotlin, Android and want to develop Android apps. It also acts as a refresher for those who have some experience in programming with A ...
Made available through: Safari, an O'Reilly Media Company.
Online resource; Title from title page (viewed April 30, 2019).
eBooks on EBSCOhost
Keywords: Android (Electronic resource); Android (Electronic resource); Application software -- Development; Mobile apps; Logiciels d'application -- Développement.; Applications mobiles; Application software -- Development; Mobile apps